Morphogenesis and aggressiveness of cervix carcinoma - Elena Izquierdo-Kulich; Margarita Amigó de Quesada; Carlos Manuel Pérez-Amor; José Manuel Nieto-Villar (Mathematical Biosciences and Engineering)
A mathematical model was obtained to describe the relation between the tissue morphology of cervix carcinoma and both dynamic processes of mitosis and apoptosis, and an expression to quantify the tumor aggressiveness, which in this context is associated with the tumor growth rate. The proposed model was applied to Stage III cervix carcinoma in vivo studies. In this study we found that the apoptosis rate was signicantly smaller in the tumor tissues and both the mitosis rate and aggressiveness index decrease with Stage III patients’ age. These quantitative results correspond to observed behavior in clinical and genetics studies.